Structural and acoustic behavior of a timber slab with wooden tuned mass dampers - Theresa Müller; Anna Krtschil; Michael Mahler; Jan Knippers; Philip Leistner (Journal of Low Frequency Noise, Vibration and Active Control)
The increasing use of timber in multi-story construction has highlighted challenges related to the vibration behavior of timber floor slabs, affecting both structural and acoustic performance. Floor vibrations between 0 and 20 Hz and structure-borne sound especially between 50 and 100 Hz are impairing the user comfort and serviceability. This paper investigates a mono-material approach using wooden tuned mass dampers (TMDs) to reduce these vibrations in timber slabs, particularly in buildings with long spans. Eigenmodes in relevant frequency ranges are first identified, followed by the separate design and interdisciplinary integration of TMDs for structural and acoustic performance. The study integrates acoustic and structural design requirements through an interdisciplinary process, employing both experimental and numerical models. Results demonstrate that wooden TMDs can address both disciplines and reduce deflection in timber slabs and improve structure-borne and low-frequency sound transmission.